Characteristics of physical performance in professional female soccer athletes during a national competition - Domingues, H. C.; Soares, A. L. C.; Gonet, D. T.; Gomes, P. S. C. (Journal of Human Sport & Exercise, 2025)
Objectives: Identify the descriptive characteristics of physical performance in different positions, compare physical performance between the first and second half of the match, and determine the association between physical performance variables in professional female soccer athletes during a national competition. Method: Fourteen professional women's soccer players participated in the study. Data from fifteen matches of the A1 division of the 2023 Brazilian Championship were collected using GPS devices. Athletes who participated in at least one complete match during the championship's classificatory phase were included. Results: The forwards and midfielders have covered greater distances at high and low intensity and maintained a higher average speed than the other positions. However, all positions have reached similar maximum speed values (25.9 ± 1.9 km/h). Significant differences were found between the first and second halves favourable to the first half for total distance ( = -9.7%; p = .002), distance per minute ( = -7.8%; p = .010), and sprint distance ( = -11.4%; p = .000), but not for maximum speed ( = -0.4%; p = .728). Pearson's correlation coefficient indicated associations between physical performance variables ranging from 0.567 to 0.850. Conclusions: Based on a descriptive analysis, it is suggested that different positions of professional female soccer athletes presented different physical demands during the competition. Lower performance was observed in the second half compared to the first for total distance, distance per minute, and sprint distance, but not for maximum speed. Moderate to high associations were also observed between physical performance variables.